2019
DOI: 10.4103/sja.sja_17_19
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low dose bupivacaine with intrathecal fentanyl for cesarean section on maternal hemodynamic: Systemic review and meta-analysis

Abstract: Hypotension during spinal Anesthesia is the most common complication with maternal and neonatal morbidity and mortality. Low dose bupivacaine with intrathecal fentanyl is recommended as strategy to prevent spinal Anesthesia induced hypotension and related complications. The aim of this systemic review is to evaluate the efficacy of low dose bupivacaine with Intrathecal fentanyl on the improvement of maternal and neonatal outcomes compared to conventional dose bupivacaine among mothers who undergone cesarean se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Low dose spinal anesthesia can reduce the hypotensive effect as proven by the research of Chandra et al It can be an option to facilitate caesarean section in patients with cardiac disorders such as Eisenmenger syndrome. [9][10][11]18,19 Hartono et al reported a similar case.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Low dose spinal anesthesia can reduce the hypotensive effect as proven by the research of Chandra et al It can be an option to facilitate caesarean section in patients with cardiac disorders such as Eisenmenger syndrome. [9][10][11]18,19 Hartono et al reported a similar case.…”
Section: Discussionmentioning
confidence: 84%
“…In spite of these two anesthetic options, low dose spinal anesthesia can be an alternative and has been shown to reduce the effects of intraoperative hypotension. [7][8][9][10][11]…”
Section: Introductionmentioning
confidence: 99%
“…Brachytherapy is usually used to treat prostate, breast, brain, and cervical cancers. 4 Based on the speed of dosing, brachytherapy can be divided into two techniques, namely high-dose-rate (HDR) and lowdose-rate (LDR). 4,5 Spinal anesthesia techniques are generally suitable for surgical procedures involving the lower abdomen, perineum, and lower extremities.…”
Section: Introductionmentioning
confidence: 99%
“…4 Based on the speed of dosing, brachytherapy can be divided into two techniques, namely high-dose-rate (HDR) and lowdose-rate (LDR). 4,5 Spinal anesthesia techniques are generally suitable for surgical procedures involving the lower abdomen, perineum, and lower extremities. [6][7][8] A local anesthetic solution injected into the intrathecal space prevents the conduction of impulses along motor, sensory, and autonomic nerves.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systemic review and meta-analysis of Ten Randomized trials show Incidence of hypotension was less likely in mothers who received low dose bupivacaine with Fentanyl as compared to those with conventional dose of bupivacaine alone (RR = 0.43, 95% confidence interval (CI) 0.12–0.47, ten trials, 552 participants). The review revealed that Low dose bupivacaine combined with intrathecal Fentanyl decrease the incidence of hypotension [ 15 ].…”
Section: Introductionmentioning
confidence: 99%